EKSPERIMEN UJI BENDING PADA KOMPOSIT RESIN POLYESTER DAN EPOXY SERAT JERAMI PADI DENGAN PROSES HAND LAY UP - Chaerul Gautama; Muhammad Fa’iz Alfatih; Sabri Alimi (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
The use of composite materials is currently growing, composites have the advantages of low density, corrosion resistance, environmental friendliness and a simple manufacturing process. Composite is a material composed of two main ingredients, namely the matrix (binding material) and filler (filler material). In this study, the filler used was rice straw while the matrix was epoxy resin and polyester resin. The object of this research is to make and carry out a series of tests on straw fiber composite materials with variations in fiber length of 15 mm and 25 mm made by the hand lay up method. The test was carried out to determine the strength of the material and also to recalculate the weight fraction of the actual rice straw fiber resin composite to be compared with the initial volume fraction of 20% straw. The results on composite materials using polyester resin are stronger than epoxy, judging from the average price of polyester with a fiber length of 15 mm, namely the bending strength of 32.04 MPa. Calculation of weight fraction of rice straw fiber resin composite by hand lay up process with epoxy resin is 38.75 gr, while polyester resin is 24.59 gr